Algorithm And Software For Creating An Automated Diagnostic System Of The "Riodoraku" Method For Assessing Energy Imbalance In Meridians (The Peerian Journal, 2022)
Nakatani (1950), a Japanese scientist with knowledge of ancient Chinese medicine "Riodoraku" (Japanese: rio - good, do - electrical conductivity, raku - channel). created the method and recommended its use in medicine. Having created his own equipment, J. Nakatani measured the biophysical parameter, i.e. electrical resistance, from the bioactive points in the existing meridians (channels) of the patient's body. Compared to healthy people, he found that the amount of electrical resistance in the existing bioactive points in the patient's body is in the minimum-maximum state from the normal corridor. As a result: it was found that there are such informative bioactive points in each meridian, the amount of electrical resistance in the meridians is equal to the arithmetic mean value, and this means that the meridians are healthy in a normal state. J. Nakatani (1950) criteria, algorithm and software of the "Riodoraku" method were created by the author